Macroprudential policy and the revolving door of risk: Lessons from leveraged lending guidance - Kim, Sooji; Plosser, Matthew C.; Santos, João A.C. (Journal of Financial Intermediation, 2018)
We investigate the U.S. experience with macroprudential policies by studying the interagency guidance on leveraged lending. We find that the guidance primarily impacted large, closely supervised banks, but only after supervisors issued important clarifications. It also triggered a migration of leveraged lending to nonbanks. While we do not find that nonbanks use more lax lending policies than banks, we unveil important evidence that nonbanks increased bank borrowing following the guidance, possibly to finance their growing leveraged lending. The guidance was effective at reducing banks’ leveraged lending activity, but it is less clear whether it accomplished its broader goal of reducing the risk that these loans pose for the stability of the financial system. Our findings highlight the importance of supervisory monitoring for macroprudential policy goals, and the challenge that the revolving door of risk poses to the effectiveness of macroprudential regulations.